Isolation and identification of bioactive compounds from Juniperus oxycedrus L. plant grown in Iraq - Naser, Estabraq Hussein; Sarmed H. Kathem (Iraqi Journal of Pharmaceutical Sciences, 2024)
Plant extracts are differ in quality and quantity of crud extract according to the extraction solvent, extraction time, and temperature. Herbal medicine used during the history for prevention and treatment of illnesses and promotion of health also used for enhancing the quality and span of our life. Juniperus oxycedrus banches and leaves are extracted with methanol using soxhlet apparatus to extract the polar compounds according to like dissolve like rule. The flavonoids components of type flavonol, as rutin, quercetin, and catechin, as well as flavone, as apigenin, were present in the crude extract that was extracted by preparative HPLC. The isolated compounds are examined using the UV spectrum, FT IR spectrum, mass spectrum by comparing the base peak mass m/z, and HPLC by comparing the retention times of the isolated and matching compounds.